2003
DOI: 10.1094/pdis.2003.87.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, Moisture, and Seed Treatment Effects on Rhizoctonia solani Root Rot of Soybean

Abstract: The effects of temperature and soil moisture on infection and disease development by Rhizoctonia solani on soybean were studied individually. In addition, the anastomosis group of R. solani isolates recovered from soybean from 35 fields in 15 counties was determined. All of the 44 isolates recovered in this study were AG-2-2 IIIB. Five isolates of R. solani were able to infect and colonize soybean roots and hypocotyls at 20, 24, 28, and 32°C in growth chamber studies. The temperatures evaluated in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 16 publications
3
66
1
3
Order By: Relevance
“…Likewise, total precipitation for May and June 2002 was 291.1 mm, which was 117.5 and 85.6 mm higher than in 2001 and 2003, respectively. Relatively cool and wet soil conditions are considered favorable for the pathogen, and adversely affect germination and establishment of seedlings by predisposing the plants to infection for a longer period (Dorrance et al 2003). The results of this study support Teo et al (1988), who reported that higher disease incidence at higher soil *, ** Significant at P < 0.05, and P < 0.01 level, respectively; -indicates no data collected.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Likewise, total precipitation for May and June 2002 was 291.1 mm, which was 117.5 and 85.6 mm higher than in 2001 and 2003, respectively. Relatively cool and wet soil conditions are considered favorable for the pathogen, and adversely affect germination and establishment of seedlings by predisposing the plants to infection for a longer period (Dorrance et al 2003). The results of this study support Teo et al (1988), who reported that higher disease incidence at higher soil *, ** Significant at P < 0.05, and P < 0.01 level, respectively; -indicates no data collected.…”
Section: Resultssupporting
confidence: 80%
“…Anchor (carbathiin plus thiram) and Vitaflo-280 (carbathiin plus thiram), were the only two seed treatment products available for soybean at the time of this research (OMAFRA 2001). The efficacy of these seed treatments, based on plant emergence or disease incidence, was found to be variable and dependent on disease pressure and environmental conditions (Dorrance et al 2003). There is a lack of scientific results supporting the benefit of these seed treatments in terms of yield under R. solani inoculated field conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to [7] and [8] although not always consistently, fungicide seed treatments have been shown to provide protection to soybean against stand or yield reductions caused by seedling diseases in certain instances.…”
Section: Average Leaf Number and Shoot Length Of Onion As Affected Bymentioning
confidence: 99%
“…Moreover, soybean seeds treated with thiram reduced the incidence of Phomopsis sojae and increased seed germination (Hepperly and Sinclair 1978). In studies on the control of R. solani, Martin et al (1984) demonstrated differences in sensitivity to different fungicides among R. solani isolates, and Dorrance et al (2003) assessed five fungicide seed treatments to control R. solani on soybean in the greenhouse. However, none of the evaluated seed treatments completely controlled the four tested isolates.…”
Section: Introductionmentioning
confidence: 99%